Tuning the electrical transport of type II Weyl semimetal WTe2 nanodevices by Mo doping. (12th February 2018) - Fu, Dongzhi; Pan, Xingchen; Bai, Zhanbin; Fei, Fucong; Umana-Membreno, Gilberto A; Song, Honglian; Wang, Xuelin; Wang, Baigeng; Song, Fengqi
Abstract: We fabricated nanodevices from Mox W1−x Te2 (x = 0, 0.07, 0.35), and conducted a systematic comparative study of their electrical transport. Magnetoresistance measurements show that Mo doping can significantly suppress mobility and magnetoresistance. The results for the analysis of the two band model show that doping with Mo does not break the carrier balance. Through analysis of Shubnikov–de Haas oscillations, we found that Mo doping also has a strong suppressive effect on the quantum oscillation of the sample, and the higher the ratio of Mo, the fewer pockets were observed in our experiments. Furthermore, the effective mass of electron and hole increases gradually with increasing Mo ratio, while the corresponding quantum mobility decreases rapidly.